An algebra problem by Rahil Sehgal

Algebra Level 4

Let x 0 , 1 x\ne0,1 be a real number such that f 0 ( x ) = 1 1 x f_0 (x) = \dfrac1{1-x} and f n + 1 ( x ) = f 0 ( f n ( x ) ) f_{n+1}(x) = f_0 (f_n (x)) for n = 0 , 1 , 2 , n = 0,1,2,\ldots .

Find the value of f 100 ( 3 ) + f 1 ( 2 3 ) + f 2 ( 3 2 ) f_{100} (3) + f_1 \left( \dfrac23\right) + f_2 \left( \dfrac32\right) .

Give your answer truncated to 2 decimal places.


The answer is 1.66.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rahil Sehgal
Mar 24, 2017

Md Zuhair
Mar 24, 2017

f 0 ( x ) = 1 1 x f 1 ( x ) = f 0 ( f 0 ( x ) ) = 1 1 1 1 x = 1 x x = x 1 x = 1 1 x f 2 ( x ) = 1 1 1 + 1 x = x f 3 ( x ) = f 0 ( x ) f n ( x ) = f n 3 ( x ) = { 1 1 x if n mod 3 = 0 1 1 x if n mod 3 = 1 x if n mod 3 = 2 \begin{aligned} f_0(x) & = \frac 1{1-x} \\ f_1(x) & = f_0(f_0(x)) = \frac 1{1-\frac 1{1-x}} = \frac {1-x}{-x} = \frac {x-1}{x} = 1-\frac 1x \\ f_2(x) & = \frac 1{1-1+\frac 1x} = x \\ f_3(x) & = f_0(x) \\ \implies f_n (x) & = f_{n-3} (x) = \begin{cases} \dfrac 1{1-x} & \text{if } n \text{ mod 3} = 0 \\ 1 -\dfrac 1x & \text{if } n \text{ mod 3} = 1 \\ x & \text{if } n \text{ mod 3} = 2 \end{cases} \end{aligned}

f 100 ( 3 ) + f 1 ( 2 3 ) + f 2 ( 3 2 ) = f 1 ( 3 ) + f 1 ( 2 3 ) + f 2 ( 3 2 ) = 1 1 3 + 1 3 2 + 3 2 = 5 3 1.66 \begin{aligned} \implies f_{100}(3) + f_1\left(\frac 23\right) + f_2\left(\frac 32\right) & = f_1(3) + f_1\left(\frac 23\right) + f_2\left(\frac 32\right) \\ & = 1 - \frac 13 + 1 - \frac 32 + \frac 32 \\ & = \frac 53 \approx \boxed{1.66} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...